Community-based maternal, newborn, and child health surveillance: perceptions and attitudes of local stakeholders towards using mobile phone by village health volunteers in the Kenge Health Zone, Democratic Republic of Congo - Mulamba Diese; Albert Kalonji; Bibiche Izale; Susie Villeneuve; Ngoma Miezi Kintaudi; Guy Clarysse; Ngashi Ngongo; Abel Mukengeshayi Ntambue (BMC, 2018)
Abstract Background In early 2016, we implemented a community-based maternal, newborn, and child health (MNCH) surveillance using mobile phones to collect, analyze, and use data by village health volunteers (VHV) in Kenge Health Zone (KHZ), in the Democratic Republic of Congo (DRC). The objective of this study was to determine the perceptions of households, attitudes of community health volunteers, and opinions of nurses in Health center and administrative authorities towards the use of mobile phones for MNCH surveillance in the rural KHZ in the DRC. Methods We used mixed methods combining phenomenological and descriptive cross-sectional study. Between 3 and 24 March 2016, we collected the data through focus group discussions (FGD) with households, and structured interviews with VHV, local health and administrative authority, and nurses to explore the perceptions on MNCH surveillance using mobile phone. Data from the FGD and interviews  were analyzed using thematic analysis techniques and descriptive statistics respectively. Results Health issues and services for under-five children were well known by community; however, beliefs and cultural norms contributed to the practices of seeking behavior for households. Mobile phones were perceived as devices that render quick services for people who needed help; and the community's attitudes towards the mobile phone use for collection of data, analysis, and use activities were good. Although some of community members did not see a direct linkage between this surveillance approach and health benefits, majority believed that there would be better MNCH services with the use of mobile phone. In addition, VHV will benefit from free healthcare for households and some material benefits and training. The best time to undertake these activities were in the afternoon with mother of the child, being the best respondent at the household. Conclusion Health issues and services for under-five children are well known and MNCH surveillance using mobile phone by VHV in which the mother can be involved as respondent is accepted.